The Problems of Nationality and Preservation of Proverbs (On the Basis of A. Kadiri`S Novel “Days Gone By”) - T, Kobilova F.; Sh, Sharopova G. (International Journal on Orange Technologies, 2022)
When it comes to the linguocultural features of proverbs, of course, we cannot help but talk about the specific national character and mentality of nations. Because folk proverbs, which concisely convey the culture, history and customs of the people, are at the forefront of expressing the mentality of the people. The article analyzes the linguocultural features of some proverbs in English and Uzbek, shows the unique national traditions of both peoples, the expression of the specific national character in everyday life. Basically, through critical analysis of proverbs in both languages, we try to explore more of their differences and express the commonalities of their similarities using the necessary resources.